Fatigue score as a promising complementary training monitoring tool: a pilot study in elite rugby sevens players - Makni, E.; Bouaziz, T.; Chamari, K.; Tarwneh, R.; Moalla, W.; Elloumi, M. (Biology of Sport, 2023)
The aim of this study was to compare physical and hormonal responses of seventeen elite rugby sevens players over a 6-week intense training block (IT) and a consecutive 2-week tapering period (TAP), using a fatigue cut-off score of 20 as a potential moderating variable. Training was monitored by daily training load (TL) and strain (TS) (using the session rating of perceived exertion [sRPE]) and also the weekly total score of fatigue (TSF; 8-item questionnaire tool). Testing and 24 h urinary cortisol (CL), cortisone (CN), adrenaline (AD) and noradrenalin (NAD) concentrations were also analysed before (T0) and after IT (T1) and after the TAP (T2). Players were assigned to group 1 with a TSF above 20 (G1 > 20, n = 9) and group 2 with a TSF below 20 (G2 < 20, n = 8) according to the French Society for Sports Medicine guidelines. TSF (effect size [ES] from 1.17 to 1.75), TL (ES from 0.81 to 1.06) and TS (ES from 1.23 to 1.40) were higher in G1 > 20 than in G2 < 20 over IT. Likewise, performance standards (ES from 1.58 to 2.61) and AD levels were lower (ES = 3.20), whereas CL and CL/CN ratio (ES from 1.60 to 3.47) were higher in G1 > 20 than in G2 < 20. After the TAP, TSF, TL and TS returned to baseline values for both groups, with an increase in performance standards and normalization in hormone levels. We suggest that a TSF greater than or equal to 20 could be considered as a fatigue threshold generating hormone disturbance and performance decrement, making it a potentially useful preventive and complementary training monitoring tool.